2011
DOI: 10.1111/j.1447-0594.2011.00772.x
|View full text |Cite
|
Sign up to set email alerts
|

Evaluation of a Japanese version of the Mini‐Mental State Examination in elderly persons

Abstract: We found that the MMSE had multiple cognitive areas. We showed that the MMSE could be used as an essentially unidimensional measure of cognitive ability and the question about orientation to time might be useful in the simplest assessment to identify cognitive dysfunction.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

0
79
0
1

Year Published

2013
2013
2021
2021

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 101 publications
(80 citation statements)
references
References 10 publications
0
79
0
1
Order By: Relevance
“…Moreover, in Korea, different versions of the MMSE were developed by different groups [16, 32, 33]. Furthermore, as time goes by, revised and modified versions of the MMSE are derived [34–37, 40]. This study is limited in that we selected only one version of the MMSE per country for comparison.…”
Section: Discussionmentioning
confidence: 99%
“…Moreover, in Korea, different versions of the MMSE were developed by different groups [16, 32, 33]. Furthermore, as time goes by, revised and modified versions of the MMSE are derived [34–37, 40]. This study is limited in that we selected only one version of the MMSE per country for comparison.…”
Section: Discussionmentioning
confidence: 99%
“…Desde então, pesquisas internacionais (Abraham et al, 1994;Baños & Franklin, 2002;Braekhus, Laake, & Engedal, 1992;Brugnolo et al, 2009;Commenges et al, 1992;Ideno, Takayama, Hayashi, Takagi, & Sugai, 2012;Jones & Gallo, 2000;Tinklenberg et al, 1990) e nacionais (CastroCosta et al, 2009(CastroCosta et al, , 2014 têm investigado a estrutura interna do exame por meio de análises fatoriais exploratórias e/ou confirmatórias e de componentes principais.…”
unclassified
“…Moreover, in Korea, different versions of the MMSE were developed by different groups [16,32,33]. Furthermore, as time goes by, revised and modified versions of the MMSE are derived [34][35][36][37]40]. This study is limited in that we selected only one version of the MMSE per country for comparison.…”
Section: Discussionmentioning
confidence: 99%
“…Previous studies have reported that the MMSE total score was affected by age and education, and normative data were provided for age and education [2,[38][39][40]. In a Korean version of the MMSE (MMSE-K) [34], 4 additional points were given to illiterate patients.…”
Section: Discussionmentioning
confidence: 99%